The Role of Mitochondria from Mature Oocyte to Viable Blastocyst. (16th May 2013) - Chappel, Scott
Abstract : The oocyte requires a vast supply of energy after fertilization to support critical events such as spindle formation, chromatid separation, and cell division. Until blastocyst implantation, the developing zygote is dependent on the existing pool of mitochondria. That pool size within each cell decreases with each cell division. Mitochondria obtained from oocytes of women of advanced reproductive age harbor DNA deletions and nucleotide variations that impair function. The combination of lower number and increased frequency of mutations and deletions may result in inadequate mitochondrial activity necessary for continued embryo development and cause pregnancy failure. Previous reports suggested that mitochondrial activity within oocytes may be supplemented by donor cytoplasmic transfer at the time of intracytoplasmic sperm injection (ICSI). Those reports showed success; however, safety concerns arose due to the potential of two distinct populations of mitochondrial genomes in the offspring. Mitochondrial augmentation of oocytes is now reconsidered in light of our current understanding of mitochondrial function and the publication of a number of animal studies. With a better understanding of the role of this organelle in oocytes immediately after fertilization, blastocyst and offspring, mitochondrial augmentation may be reconsidered as a method to improve oocyte quality.